Comparing phonology of dyads of children with typical development and protracted development. (September 2013) - Dubasik, Virginia L.; Ingram, David
Abstract: This study compares data from three functionally monolingual Spanish-speaking children with protracted phonological development (PPD; Chávez-Peón et al., 2012) and three language- and age-matched children with typical development (TD) at two time points to highlight similarities and differences in patterns of production. Spanish data were analyzed using an adapted version of Ingram and Ingram's Basic Analysis and an assessment of phonological similarity. Results indicate that children differed with regard to phonology at both time points. Children with PPD evidenced less developed skills at both time points and varying development across aspects. Differences within and between children were highlighted when examining scores over time. Aspects of the children's phonologies at Time 1 showed varying degrees of positive change at Time 2. These data are consistent with previous research, and additionally offer specific information gleaned from innovative analyses, which may prove to be useful in future research.